Anode Compositions Including Crosslinkable Binders

The aqueous anode composition with polycarboxylic acid polymer and alcohol or amine enhances mechanical strength and electrochemical resistance, addressing crosslinking challenges and reducing harmful compound use for efficient anode production.

JP2025500127AInactive Publication Date: 2025-01-09COATEX SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024530479
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-20
Filing Date
2022-12-19
Publication Date
2025-01-09
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing anode compositions face issues with mechanical strength, electrochemical resistance, strain tolerance, and the need for controlled crosslinking reactions, often involving harmful compounds like phosphorus-containing substances, which affect manufacturing time and efficiency.

Method used

An aqueous anode composition using a crosslinkable composition comprising polycarboxylic acid polymer with alcohol or amine, combined with carbon or metal particles, avoids phosphorus compounds and includes specific polymerization and neutralization processes to enhance binding and crosslinking properties.

Benefits of technology

The solution provides improved mechanical strength, electrochemical resistance, and controlled crosslinking, reducing manufacturing time and environmental impact while maintaining high reaction rates and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500127000001
    Figure 2025500127000001
  • Figure 2025500127000002
    Figure 2025500127000002
  • Figure 2025500127000003
    Figure 2025500127000003
Patent Text Reader

Abstract

The present invention relates to an aqueous anode composition comprising carbon or metal particles and a crosslinkable composition comprising a polycarboxylic acid polymer in combination with an alcohol or an amine. The present invention also relates to a method of making an anode using said aqueous composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous anode composition comprising carbon or metal particles and a crosslinkable composition comprising a polycarboxylic acid polymer in combination with an alcohol or an amine. The present invention also relates to a method of making an anode using said aqueous composition. [Background technology]

[0002] Anode compositions are known that generally comprise carbon or metal in the form of particles associated with a binder composition. The most common binder compositions comprise styrene-butadiene polymers. After crosslinking, the composition makes it possible to fix the particles on the metal substrate. Bonding properties are therefore crucial when using these anode compositions to manufacture anodes. Furthermore, mechanical strength or electrochemical resistance are particularly desired.

[0003] These anode compositions often contain silicon to increase the capacity of the prepared anode.During the charge-discharge cycle of the battery containing these anodes, strain is usually observed, which can lead to irreversible changes in the anode.Therefore, strain tolerance is also a desirable property.

[0004] The reactions involved in the crosslinking of the composition must also be effectively controlled. Parasitic reactions or inhibition of the reagents used must be avoided. The formation of decomposition or colored by-products, especially as a result of excessive exposure to high temperatures, must be reduced or avoided. These crosslinkable compositions should be highly reactive. They should allow high reaction rates.

[0005] The time required to fabricate these anodes is also an important factor, and therefore it is important to improve the efficiency of the various reactions involved, especially when crosslinking the anode composition.

[0006] It should also be possible to reduce the number of components used in preparing the anode composition.

[0007] Known crosslinkable compositions are used in many fields. However, some compounds should be avoided or removed from these crosslinkable compositions, especially for reasons of efficacy and safety, but also for economic or environmental reasons. It may also be advantageous to be able to omit phosphorus compounds when preparing the reagents for the crosslinkable composition, or when preparing the crosslinkable composition, or when applying it before crosslinking. It should therefore be possible to prepare esters or amides for the crosslinkable composition in the absence of any compound that may be considered harmful from an environmental point of view, or in the absence of any compound whose use is restricted by regulatory agencies. In particular, it may be preferable to prepare these compounds in the absence of any compound containing phosphorus, especially in the absence of phosphorus in either oxidation state I, III or V.

[0008] The reactions involved in the cross-linking of the compositions present on the material must also be effectively controlled: parasitic reactions or inhibition of the reagents used must be avoided.

[0009] It is also important to have access to the improved tools necessary to prepare the anode, particularly crosslinkable aqueous compositions or crosslinking agents.

[0010] The time required to prepare these complexes is also an important factor, therefore it is important to improve the efficiency of the various reactions involved, especially during crosslinking.

[0011] Document JP2021015778 describes an electrode binder comprising polyacrylic acid with a molecular weight of 1.5 million g / mol and a polyol or aminoalcohol copolymer. Document CN112993252 describes a crosslinkable anode binder composition comprising a polyacrylic acid polymer with a molecular weight of 200,000 g / mol, a carboxylic acid elastomer and a crosslinking polyol. Document EP1300426 describes the preparation of (meth)acrylic acid copolymers and polyethoxylated isoprenol copolymers in the presence of bisulfite and persulfate.

[0012] Prior art anode compositions have not always been satisfactory. Thus, there is a need for an anode composition that provides a solution to all or part of the problems of prior art anode compositions. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Patent Publication No. 2021-015778 [Patent Document 2] China Patent Application Publication No. 112993252 [Patent Document 3] European Patent Application Publication No. 1300426 Summary of the Invention

[0014] Thus, the present invention provides an aqueous anode composition T comprising: at least one crosslinkable aqueous composition R, which comprises: a) at least one polymer A prepared in water by polymerization reaction of at least one monomer M selected from acrylic acid, methacrylic acid, acrylates, methacrylates and combinations thereof in the presence of at least one initiator compound; b) at least one compound B selected from polyols, polyamines, aminoalcohols, (polyamino)alcohols, amino(polyalcohols), ose, oside and combinations thereof; A crosslinkable aqueous composition comprising: At least one material E selected from metal fibers, metal particles, carbon-graphite fibers, carbon-graphite particles, and combinations thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Essentially, for the purposes of the present invention, polymer A is prepared using monomer M. Preferably, according to the present invention, monomer M is selected from acrylic acid, acrylates and combinations thereof.

[0016] According to the present invention, the monomer M can be combined with at least one other monomer, preferably another monomer selected from vinyl acetate, ethyl acrylate, methyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), maleic acid, maleic anhydride, itaconic acid, and combinations thereof. When combined with another monomer, the monomer M can be selected from acrylic acid, acid salts, and combinations thereof, in combination with at least one other monomer selected from vinyl acetate, ethyl acrylate, methyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), maleic acid, maleic anhydride, itaconic acid, and combinations thereof. In combination with another monomer, the amount by weight of the other monomer is less than the amount by weight of the monomer M. Preferably, according to the present invention, the monomer M is acrylic acid alone.

[0017] Preferably, the polymerization reaction is carried out at a temperature above 30° C. and below 130° C., preferably below 100° C. or below 90° C. or below 80° C. or below 75° C. Preferably, during the polymerization reaction to prepare polymer A, the initiator compound is selected from peroxides (e.g., hydrogen peroxide), hydroperoxides (e.g., tert-butyl hydroperoxide), persulfates (e.g., sodium persulfate, ammonium persulfate, potassium persulfate), combinations thereof, and their associations with metal salts, preferably selected from iron salts (e.g., FeII or FeIII), copper salts (e.g., CuI or CuII), and combinations thereof.

[0018] Preferably, polymer A has a weight average molecular weight Mw (measured by SEC) of less than 1 million g / mol or less than 800,000 g / mol, preferably less than 400,000 g / mol or less than 200,000 g / mol, more preferentially less than 50,000 g / mol or less than 20,000 g / mol, more preferably less than 15,000 g / mol or less than 10,000 g / mol, even more preferentially less than 7,000 g / mol or less than 6,000 g / mol. Polymer A generally has a weight average molecular weight Mw (measured by SEC) of greater than 1,000 g / mol or greater than 1,200 g / mol.

[0019] Preferably, polymer A has a polymolecularity index IP (measured by SEC) of less than 4 or in the range from 1.2 to 4 or from 1.5 to 4, from 1.2 to 3 or from 1.5 to 3, from 1.2 to 2.5, or even from 1.5 to 2.5.

[0020] According to the invention, the molecular weight or mass of polymer A is determined by size exclusion chromatography (SEC). A test portion of the polymer solution corresponding to 90 mg of dry solid is placed in a 10 mL flask. The mobile phase is added with 0.04% dimethylformamide (DMF) until a total mass of 10 g is reached. The composition of this mobile phase is as follows: NaHCO3: 0.05 mol / L, NaNO3: 0.1 mol / L, triethanolamine: 0.02 mol / L, NaN3: 0.03 wt.%. The SEC chain consists of a Waters 510 isocratic pump with a flow rate set at 0.8 mL / min, a Waters 717+ sample changer, an oven containing a Waters Ultrahydrogel Column Guard precolumn 6 cm long and 40 mm internal diameter, followed by a Waters Ultrahydrogel linear column 30 cm long and 7.8 mm internal diameter. Detection is performed using a Waters 410 RI differential refractometer. The oven is brought to a temperature of 60 °C and the refractometer to a temperature of 45 °C. The SEC instrument is calibrated with a series of sodium polyacrylate standards supplied by Polymer Standard Service, with molecular weights at the top of the peaks comprised between 900 and 2,250,000 g / mol and polymolecularity indices comprised between 1.4 and 1.7. The calibration curve is linear and takes into account the correction obtained with the flow marker dimethylformamide (DMF). The acquisition and processing of the chromatograms are carried out using the PSS WinGPC Scientific software v4.02. The chromatograms obtained are fitted into the zone corresponding to molecular weights above 250 g / mol.

[0021] According to the invention, polymer A can be unneutralized or partially or completely neutralized. Preferably, polymer A is unneutralized. According to the invention, the carboxyl groups of polymer A can be partially neutralized in a proportion of 70-97 mol %, preferably in a proportion of 90-95 mol %. Polymer A can be partially or completely neutralized by at least one monovalent ion or at least one divalent ion. According to the invention, polymer A can be partially or completely neutralized by a combination of at least one monovalent ion and at least one divalent ion. Then, according to the invention, polymer A can be completely or partially neutralized with a variable relative molar ratio of monovalent and divalent ions. Preferably, according to the invention, the molar ratio of monovalent ions / divalent ions is comprised between 90 / 10 and 10 / 90 or between 80 / 20 and 20 / 80, preferably between 80 / 20 and 60 / 40, for example 70 / 30 or 50 / 50.

[0022] According to the present invention, neutralization is carried out with a primary amine, a secondary amine or K + , Na + , Li + , NH4 + and combinations thereof. The preferred ion is NH4 + According to the present invention, the neutralization is 2+ , Mg 2+ , Zn 2+ and combinations thereof. The preferred divalent ions are Ca 2+ , Zn 2+ and combinations thereof.

[0023] According to the invention, polymer A can be neutralized by at least one compound selected from NaOH, KOH, ammonium derivatives, ammonia, primary amines, secondary amines, CaO, Ca(OH)2, MgO, Mg(OH)2, ZnO, Zn(OH)2 and combinations thereof. Neutralizing polymer A with ammonia is particularly advantageous when using composition T or composition R at a pH of less than 7, preferably less than 5. According to the invention, polymer A can be fully or partially neutralized by a base selected from amine bases, for example ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, α,α'-diaminoxylene, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, triethanolamine, aminomethylpropanol or 2-amino-2-methyl-propanol (AMP) and combinations thereof. Advantageously, according to the invention, an amine base can also be present in composition R as amine compound B.

[0024] Preferably, according to the invention, the polymer A can be prepared in the presence of at least one polymerization agent C selected from the compounds C1 to C6 and combinations thereof.

[0025] According to the invention, preferably, compound C is a sulfur compound C1 containing sulfur in oxidation state IV, preferably selected from lithium hydrogen sulfite, sodium hydrogen sulfite, potassium hydrogen sulfite, ammonium hydrogen sulfite, calcium di(hydrogen sulfite), magnesium di(hydrogen sulfite) and combinations thereof. Preferentially, according to the invention, compound C1 is a monohydrogen sulfite. According to the invention, the molar amount of sulfur compound C1, preferably the molar amount of sulfur IV, is comprised between 1% and 15%, preferably between 1.5% and 12%, relative to the total molar amount of unsaturated groups of the monomers used, and preferably the molar amount of sulfur compound C1, preferably the molar amount of sulfur IV, is comprised between 1% and 15%, preferably between 1.5% and 12%, relative to the total molar amount of unsaturated groups of the monomers used.

[0026] According to the invention, compound C can be a phosphorus compound C2 containing phosphorus in oxidation state I, preferably selected from hypophosphorous acid, sodium hypophosphite, potassium hypophosphite, lithium hypophosphite, ammonium hypophosphite, calcium hypophosphite, magnesium hypophosphite and combinations thereof. Advantageously according to the invention, when polymer A is prepared in the presence of polymerization agent C2, a phosphinocarboxylic acid polymer is obtained, so that the polymer A obtained contains phosphinate and phosphonate groups. In particular, the molar amount of phosphorus compound C2, preferably the molar amount of phosphorus I, is comprised between 1% and 15% relative to the total molar amount of monomers used, preferably the molar amount of phosphorus compound C2, preferably the molar amount of phosphorus I, is comprised between 1.5% and 12% relative to the total molar amount of unsaturated groups of the monomers used.

[0027] According to the invention, compound C can be a phosphorus compound C3 containing phosphorus in oxidation state III, preferably chosen from phosphorous acid, phosphites and combinations thereof. In particular, the molar amount of phosphorus compound C3, preferably the molar amount of phosphorus III, is comprised between 1% and 15% relative to the total molar amount of monomers used, preferably the molar amount of phosphorus compound C3, preferably the molar amount of phosphorus III, is comprised between 1.5% and 12% relative to the total molar amount of unsaturated groups of monomers used.

[0028] Preferably, according to the invention, compound C may be a secondary alcohol C4, preferably isopropyl alcohol.

[0029] Also preferably, according to the invention, compound C may be a sulfur compound C5, preferably selected from primary thiols, mercaptans and combinations thereof, such as tert-dodecyl mercaptan, tert-nonyl mercaptan, thiolactic acid, mercaptopropionic acid, mercaptoethanol, thioglycolic acid, 1,8-dimercapto-3,6-dioxaoctane (DMDO - CAS number 14970-87-7).

[0030] Also preferably, according to the invention, compound C is a RAFT polymerization agent C6, preferably dipropyltrithiocarbonate (DPTTC - CAS number 6332-91-8) or a salt thereof, such as its disodium salt (sodium dipropionate trithiocarbonate, CAS number 86470-33-2). In particular, the molar amount of compound C6, preferably the molar amount of DPTTC, is comprised between 1.5% and 12% relative to the total molar amount of monomers used, preferably the molar amount of compound C6, preferably the molar amount of DPTTC, is comprised between 1.5% and 12% relative to the total molar amount of unsaturated groups of the monomers used.

[0031] Also preferably, according to the invention, the polymer A is chosen from α-ω-disulfonated polymers A1, α-monosulfonated polymers A2, polymers A3 containing phosphinate groups, polymers A4 containing phosphonate groups, polymers A5 containing phosphinate and phosphonate groups, and combinations thereof.

[0032] According to the invention, composition T may also contain, preferably in composition R, a compound D selected from sulfo-carboxy-aromatic and sulfo-carboxy-alkyl acids, preferably 3-sulfopropionic acid, 3-sulfo-2-methyl-propionic acid, sulfo-succinic acid, their salts and combinations thereof. Preferred salts of compound D are selected from sodium, potassium, lithium, calcium, magnesium and ammonium salts. The sodium and ammonium salts of compound D are particularly preferred. Also preferably, composition T or composition R contains a molar amount of compound D, measured according to the method in the examples, of more than 2% relative to the molar amount of sulfur IV in compound C1. Preferably, according to the invention, composition T or composition R contains a molar amount of compound D, measured according to the method in the examples, of more than 5%, preferably more than 10% or more than 15%, more preferentially more than 20% or more than 25%, relative to the molar amount of sulfur IV. Also preferably, according to the invention, the molar amount of compound D, determined according to the method of the examples, is less than 60%, preferably less than 50% or less than 40%, relative to the molar amount of sulfur IV.

[0033] According to the present invention, the amount of compound D and compound D (mol % relative to the molar amount of sulfur IV of compound T used) can be determined by sulfate ion assay and by the amount of sulfonated groups of polymer A and compound D. 1 H NMR and 13 Determined by C NMR analysis.

[0034] According to the invention, the molar amount of compound D present in composition T or composition R relative to the molar amount of sulfur IV is therefore generally comprised within the range of 2% to 60% or 2% to 50% or 2% to 40%, preferably 5% to 60% or 5% to 50% or 5% to 40%. Also preferably, the molar amount of compound D present in composition T or composition R relative to the molar amount of sulfur IV is therefore generally comprised within the range of 10% to 60% or 10% to 50% or 10% to 40%. Also preferably, the molar amount of compound D present in composition T or composition R relative to the molar amount of sulfur IV is comprised within the range of 15% to 60% or 15% to 50% or 15% to 40% or even 25% to 60% or 25% to 50% or 25% to 40% or even 20% to 60% or 20% to 50% or 20% to 40%.

[0035] According to the invention, composition T may also comprise, for example in composition R, a compound F selected from 2-sulfoacetic acid, para-toluenesulfonic acid (PTSA), sulfuric acid, methanesulfonic acid, their salts and combinations thereof.

[0036] Preferably, according to the invention, compound B is selected from non-alkoxylated polyols, non-alkoxylated polyamines, non-alkoxylated amino alcohols, non-alkoxylated (polyamino) alcohols, non-alkoxylated amino (polyalcohols), non-alkoxylated oses, non-alkoxylated osides, alkoxylated polyols, alkoxylated polyamines, alkoxylated amino alcohols, alkoxylated (polyamino) alcohols, alkoxylated amino (polyalcohols), alkoxylated oses, alkoxylated osides and combinations thereof.

[0037] Also preferably, according to the invention, compound B is selected from non-alkoxylated polyols, non-alkoxylated oses, non-alkoxylated osides, alkoxylated polyols, alkoxylated oses, alkoxylated osides and combinations thereof, in particular alkoxylated polyols, non-alkoxylated polyols, non-alkoxylated oses, non-alkoxylated osides and combinations thereof.

[0038] Preferably, according to the invention, compound B may contain a number of alkoxylated groups ranging from 2 to 500, preferably from 10 to 250 or from 25 to 150. Preferably, according to the invention, the alkoxylated groups are selected from oxyethylene, oxypropylene, oxybutylene and combinations thereof. The preferred alkoxylated groups are oxyethylene, optionally combined with oxypropylene.

[0039] More preferably, according to the invention, compound B is selected from the group consisting of glycerol, polyalkylene glycol (preferably polyalkylene glycol, polypropylene glycol, polybutylene glycol), pentaerythritol, triethanolamine, ethanolamine, diethanolamine, 3-amino-1-propanol, 1-amino-2-propanol, butanetriol, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, pentaerythritol, sorbitol, 5-amino-1-pentanol, 1,2-dimethylphenylsulfonyl ether, 1,3-dimethylphenylsulfonyl ether, 1,4-dimethylphenylsulfonyl ether, 1,6 ... , 2-(2-aminoethoxy)ethanol, N-(2-aminoethyl)ethanolamine, bis(N-hydroxyethyl)propane-1,3-diamine, diisopropanolamine, triisopropanolamine, N-methyldiethanolamine, N-butyldiethanolamine, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2,3-propanetriol, 1,2-butanediol, 1,4-butanediol, 2,3-butanediol, neopentyl glycol Licor, trimethylolpropane, 1,2,4-butanetriol, 1,2-pentanediol, 1,5-pentanediol, 1,6-hexanediol, 2,5-dimethyl-2,5-hexanediol, D-arabinose, L-arabinose, D-xylose, D-glucose, D-mannose, D-galactose, D-glucosamine, D-fructose, maltose, sucrose, lactose, ethylenediamine, diethylenetriamine, triethylenetetramine, 1,3-diaminopropane, 1,2-diaminopropane, neopentyldiamine amine, hexamethylenediamine, octamethylenediamine, N-(2-aminoethyl)propane-1,3-diamine, 1,2,3-propanetriamine, N,N-bis(3-aminopropylamine) and combinations thereof, preferably selected from glycerol, triethanolamine, trimethylolpropane, 1,2,4-butanetriol, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, pentaerythritol, sorbitol and combinations thereof.Also preferably, compound B has a molecular weight in the range of 50 g / mol to 1,000 g / mol, preferably 55 g / mol to 500 g / mol or 55 g / mol to 250 g / mol.

[0040] Preferentially, according to the invention, composition T comprises a molar amount of functional groups of compound B ranging from 5% to 100%, preferably from 10% to 100% or from 10% to 90% or from 20% to 100% or from 20% to 80%, relative to the total molar amount of carboxyl groups of polymer A.

[0041] Advantageously, according to the invention, composition R comprises a molar amount of compound B ranging from 5% to 100%, preferably from 10% to 100% or from 10% to 90% or from 20% to 100% or from 20% to 80%, relative to the total molar amount of monomers.

[0042] Particularly advantageously, the invention avoids the use of certain compounds or substances. Preferably, according to the invention, composition T does not comprise any urea-formaldehyde compounds or any formaldehyde compounds. Advantageously, composition T does not comprise any compound containing phosphorus in oxidation state I, any compound containing phosphorus in oxidation state III or any compound containing phosphorus in oxidation state V. Also advantageously, composition R does not comprise any urea-formaldehyde compounds or any formaldehyde compounds, or any compound containing phosphorus in oxidation state I, any compound containing phosphorus in oxidation state III or any compound containing phosphorus in oxidation state V. Advantageously, according to the invention, composition T does not comprise any elastomer.

[0043] Preferably, according to the invention, composition T comprises a material E selected from silicon, lithium, carbon graphite or graphitic carbon, hexagonal carbon, rhombohedral carbon and combinations thereof, preferably doped with at least one element selected from lithium, germanium, silicon and combinations thereof. Preferred materials E are selected from carbon graphite, silicon and combinations thereof.

[0044] The present invention also provides a method for preparing composition T. The preparation method includes: - preparation of an aqueous composition R according to the invention, the addition of at least one material E chosen from metal fibres, metal particles, carbon graphite fibres, carbon graphite particles and combinations thereof, preferably material E chosen from silicon, lithium, carbon graphite or graphitic carbon, hexagonal carbon, rhombohedral carbon and combinations thereof, optionally doped with at least one element, preferably chosen from lithium, germanium, silicon and combinations thereof;

[0045] The present invention also provides an aqueous composition R defined according to the invention, as well as a method for preparing it, which comprises preparing a polymer A according to the invention and then adding at least one polyfunctional compound B selected from polyols, polyamines, aminoalcohols, (polyamino)alcohols, amino(polyalcohols), oses, oses and combinations thereof.

[0046] The use of the sulfur compound C1 according to the invention in preparing the polymer A results in a process for preparing a composition R, which comprises: - preparation of polymer A according to the invention, - optionally maintaining or adding to the aqueous dispersion of polymer A at least one compound D chosen from sulfocarboxylic acids, sulfocarboxylates and combinations thereof, - the addition of at least one polyfunctional compound B chosen from polyols, polyamines, aminoalcohols, (polyamino)alcohols, amino(polyalcohols), oses, oses and combinations thereof.

[0047] The use of the phosphorus compound C2 or the phosphorus compound C3 according to the invention in preparing the polymer A results in a process for preparing a composition R, which comprises: - the preparation of a polymer A according to the invention in the presence of at least one compound C2 or at least one compound C3, - optionally maintaining or adding to the aqueous dispersion of polymer A at least one compound resulting from the reaction of a monomer M with a compound C2 or with at least one compound C3, - the addition of at least one polyfunctional compound B chosen from polyols, polyamines, aminoalcohols, (polyamino)alcohols, amino(polyalcohols), oses, oses and combinations thereof.

[0048] The present invention also provides an agent for crosslinking polyfunctional compounds B, a method for improving the crosslinking properties of an aqueous composition R using compounds D according to the invention, and corresponding crosslinking improvers.

[0049] Crosslinking agents according to the invention for crosslinking the aqueous composition R include: at least one α-sulfonated polymer A prepared in water by polymerization reaction of at least one monomer M chosen from acrylic acid, methacrylic acid, acrylates, methacrylates and combinations thereof, in the presence of at least one initiator compound and at least one sulfur compound containing sulfur in oxidation state IV, preferably in the absence of any phosphorus compound, at least one compound D chosen from sulfocarboxylic acids, sulfocarboxylates and combinations thereof;

[0050] The method for improving the crosslinking properties of the aqueous composition R comprises: at least one aqueous dispersion of an α-sulfonated polymer A prepared in water by polymerization reaction of at least one monomer M chosen from acrylic acid, methacrylic acid, acrylates, methacrylates and combinations thereof, in the presence of at least one initiator compound and at least one sulfur compound containing sulfur in oxidation state IV, preferably in the absence of any phosphorus compound, at least one polyfunctional compound B chosen from polyols, polyamines, aminoalcohols, (polyamino)alcohols, amino(polyalcohols), oses, oses and combinations thereof, It comprises maintaining or adding to an aqueous dispersion or aqueous composition R of a polymer A at least one compound D chosen from sulfocarboxylic acids, sulfocarboxylates and combinations thereof.

[0051] Agents for improving the crosslinking properties of the aqueous composition R include: at least one α-sulfonated polymer A prepared in water by polymerization reaction of at least one monomer M chosen from acrylic acid, methacrylic acid, acrylates, methacrylates and combinations thereof, in the presence of at least one initiator compound and at least one sulfur compound C1 containing sulfur in oxidation state IV, preferably in the absence of any phosphorus compound, at least one compound D chosen from sulfocarboxylic acids, sulfocarboxylates and combinations thereof;

[0052] The aqueous anode composition T of the present invention can be particularly advantageously used in the manufacture of an anode. Accordingly, the present invention provides a method for the manufacture of an anode, comprising: - application onto the substrate of at least one composition T according to the invention, - Crosslinking of material E impregnated with composition R.

[0053] Preferably, when producing an anode according to the invention, at least one of the application or crosslinking steps is carried out at a pH of less than 7, preferably less than 5. Preferably, when producing an anode according to the invention, crosslinking is carried out at a temperature in the range of 100 to 250°C, preferably 150 to 240°C or 170 to 230°C.

[0054] The present invention also provides an anode prepared according to the preparation method of the present invention.

[0055] According to the invention, the particular, advantageous or preferred features of the composition T according to the invention define particular, advantageous or preferred aqueous compositions R, the preparation methods and the corresponding agents and anodes according to the invention.

[0056] The following examples illustrate various aspects of the present invention. EXAMPLES

[0057] Preparation and characterization of polymer AA according to the invention In a 1 liter glass reactor equipped with stirrer, thermometer and cooling system, a charge of 6.66 g of sodium hypophosphite in 182 g of water is introduced at room temperature. A solution of 0.01 g of iron sulfate heptahydrate in 0.74 g of water is then added, and three charges are prepared and introduced in parallel for 2 hours. In a first beaker, 224.01 g of acrylic acid are introduced. In a second beaker, 23.12 g of 35% by weight hydrogen peroxide in 19.9 g of water are introduced. In a third beaker, 6.03 g of sodium hypophosphite in 14 g of water are introduced. After an addition time of 2 hours at 97 ° C, a transparent dispersion of polymer AA is obtained, the concentration of dry solids is 45%, the mass Mw is 3,855 g / mol and the IP is 2.0.

[0058] Preparation and characterization of polymer AB according to the invention In a 1 liter glass reactor equipped with stirrer, thermometer and cooling system, a charge is prepared at room temperature containing 0.006 g of iron sulfate heptahydrate and 380 g of water. Three charges are then prepared and introduced in parallel for 3 hours. In the first beaker, 623.5 g of acrylic acid are introduced, in the second beaker, 5.086 g of sodium persulfate and 46.6 g of water are introduced, and in the third beaker, 122.86 g of a 40% by weight aqueous solution of sodium hydrogen sulfite are introduced. After an addition time of 3 hours at 73°C, a transparent dispersion of polymer AB is obtained, with a concentration of dry solids of 55.2%, a mass Mw of 4,430 g / mol and an IP of 2.2.

[0059] Preparation and characterization of polymer AC according to the present invention In a 1 liter glass reactor equipped with stirrer, thermometer and cooling system, a charge containing 0.023 g of iron sulfate heptahydrate and 284.13 g of water is prepared at room temperature. Three charges are then prepared and introduced in parallel for 3 hours. Firstly, a charge of 0.74 g of sodium persulfate and 19.68 g of water is introduced into the reactor heated to 80° C. Then, in the first beaker, 450.99 g of acrylic acid are introduced, in the second beaker, 1.96 g of sodium persulfate and 19.68 g of water, and in the third beaker, 94.23 g of a 40% by weight aqueous sodium hydrogen sulfite solution. After 3 hours of addition at 80° C., a transparent dispersion of polymer AC is obtained. The polymer is then neutralized to a pH of 2.0 by adding sodium hydroxide. The concentration of dry solids is 50.0%. The polymer AC has a mass Mw of 6,000 g / mol and an IP of 2.7.

[0060] <Preparation of Composition R According to the Present Invention> <Preparation of composition RA1 according to the present invention> 525.83 g of Polymer Dispersion AA, 2.30 g of sodium hypophosphite, 157.81 g of triethanolamine (polyfunctional compound B) and 321.60 g of water are mixed with stirring.

[0061] <Preparation of composition RA2 according to the present invention> 614.07 g of polymer dispersion AA, 3.50 g of sodium hypophosphite, 129.41 g of a 70% by weight aqueous sorbitol solution (polyfunctional compound B) and 309.34 g of water are mixed with stirring.

[0062] <Preparation of composition RB1 according to the present invention> 131.34 g of polymer dispersion AB, 22.7 g of glycerol (polyfunctional compound B) and 24.2 g of water are mixed with stirring.

[0063] <Preparation of composition RC1 according to the present invention> 146.46 g of Polymer Dispersion AC, 22.7 g of glycerol (polyfunctional compound B) and 24.2 g of water are mixed with stirring.

[0064] <Preparation and Characterization of Anode Composition T According to the Invention> <Preparation of composition TA1 according to the present invention> A homogeneous mixture is prepared containing 3.07g of composition RA1, 83.16g of deionized water and 80.75g of carbon graphite (Xiamen Tob tb-sup-c65-CAS number 1333-86-4) while stirring at 2,000 rpm (Hauschild Speed ​​mixer DAC 400 FVZ). The resulting composition TA1 has a solid content of 60.6%.

[0065] <Preparation of composition TA2 according to the present invention> A homogeneous mixture is prepared containing 3.18g of composition RA2, 51.42g of deionized water and 80.35g of carbon graphite (Xiamen Tob tb-sup-c65-CAS number 1333-86-4) while stirring at 2,000 rpm (Hauschild Speed ​​mixer DAC 400 FVZ). The resulting composition TA2 has a solid content of 60.5%.

[0066] <Preparation of composition TB1 according to the present invention> A homogeneous mixture is prepared containing 2.62g of composition RB1, 49.02g of deionized water and 70.39g of carbon graphite (Xiamen Tob tb-sup-c65-CAS number 1333-86-4) while stirring at 2,000 rpm (Hauschild Speed ​​mixer DAC 400 FVZ). The resulting composition TB1 has a solid content of 58.8%.

[0067] <Preparation of composition TC1 according to the present invention> A homogeneous mixture is prepared containing 2.56g of composition RC1, 49.02g of deionized water and 70.22g of carbon graphite (Xiamen Tob tb-sup-c65-CAS number 1333-86-4) while stirring at 2,000 rpm (Hauschild Speed ​​mixer DAC 400 FVZ). The resulting composition TC1 has a solid content of 58.7%.

[0068] A continuous homogenous layer of composition TA1 (250 μm thick-wet) is applied to a copper substrate (copper foil for the anode, 12 μm thick) using a Byko-Drive (BYK) automatic film applicator. This is allowed to dry for 24 hours at room temperature.

[0069] The layer is manually wiped off on the first sample at room temperature. Partial transfer of graphite to the finger is observed, as well as degradation of the applied layer of composition TA1. In this sample, composition TA1 does not adhere sufficiently to the copper substrate to provide mechanical strength.

[0070] The second sample was placed in a 205°C oven for 10 minutes. After cooling to room temperature, the layer was manually wiped off. This did not cause any graphite transfer to the finger and the applied layer remained intact. In this second sample, the treated TA1 composition adhered firmly to the copper substrate to provide mechanical strength.

[0071] These evaluations are replicated using compositions TA2, TB1 and TC1. Like composition TA1, these compositions TA2, TB1 and TC1 adhere well to the copper substrate and provide mechanical strength.

Claims

1. at least one crosslinkable aqueous composition R, a) at least one polymer A prepared in water by polymerization reaction of at least one monomer M selected from acrylic acid, methacrylic acid, acrylates, methacrylates and combinations thereof in the presence of at least one initiator compound; b) at least one compound B selected from polyols, polyamines, aminoalcohols, (polyamino)alcohols, amino(polyalcohols), oses, oses, and combinations thereof; A crosslinkable aqueous composition R comprising: at least one material E selected from metal fibers, metal particles, carbon-graphite fibers, carbon-graphite particles, and combinations thereof; The aqueous anode composition T comprises:

2. the monomers M are selected from acrylic acid, acrylic acid salts and combinations thereof, or the monomer M is combined with at least one other monomer selected from vinyl acetate, ethyl acrylate, methyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), maleic acid, maleic anhydride, itaconic acid and combinations thereof, or the monomer M is selected from acrylic acid, acid salts and combinations thereof, in combination with at least one other monomer selected from vinyl acetate, ethyl acrylate, methyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), maleic acid, maleic anhydride, itaconic acid and combinations thereof, or Composition T according to claim 1, in which polymer A is not neutralized or polymer A is partially or completely neutralized.

3. 3. Composition T according to claim 1 or 2, in which the polymer A is prepared in the presence of at least one polymerization agent C chosen from: sulfur compounds C1 containing sulfur in the oxidation state IV, preferably selected from lithium bisulfite, sodium bisulfite, potassium bisulfite, ammonium bisulfite, calcium di(bisulfite), magnesium di(bisulfite) and combinations thereof, or a phosphorus compound C2 containing phosphorus in oxidation state I, preferably selected from hypophosphorous acid, sodium hypophosphite, potassium hypophosphite, lithium hypophosphite, ammonium hypophosphite, calcium hypophosphite, magnesium hypophosphite and combinations thereof, or a phosphorus compound C3 containing phosphorus in the oxidation state III, preferably selected from phosphorous acid, phosphites and combinations thereof, or a secondary alcohol C4, preferably isopropyl alcohol, or sulfur compounds C5, preferably selected from primary thiols, mercaptans and combinations thereof, such as tert-dodecyl mercaptan, tert-nonyl mercaptan, thiolactic acid, mercaptopropionic acid, mercaptoethanol, thioglycolic acid, 1,8-dimercapto-3,6-dioxaoctane (DMDO-CAS No. 14970-87-7), or RAFT polymerization agent C6, preferably dipropyltrithiocarbonate (DPTTC-CAS No. 6332-91-8) or its salts, - and combinations thereof.

4. the molar amount of sulfur compound C1, preferably of sulfur IV, is comprised between 1% and 15%, preferably between 1.5% and 12%, relative to the total molar amount of monomers used, preferably the molar amount of sulfur compound C1, preferably of sulfur IV, is comprised between 1% and 15%, preferably between 1.5% and 12%, relative to the total molar amount of unsaturated groups of the monomers used, or the molar amount of phosphorus compound C2, preferably of phosphorus I, is comprised between 1% and 15%, relative to the total molar amount of monomers used, preferably the molar amount of phosphorus compound C2, preferably of phosphorus I, is comprised between 1.5% and 12%, relative to the total molar amount of unsaturated groups of the monomers used, or the molar amount of phosphorus compound C3, preferably the molar amount of phosphorus III, is comprised between 1% and 15%, relative to the total molar amount of monomers used, preferably the molar amount of phosphorus compound C3, preferably the molar amount of phosphorus III, is comprised between 1.5% and 12%, relative to the total molar amount of unsaturated groups of the monomers used, or Composition T according to any one of claims 1 to 3, wherein the molar amount of compound C6, preferably the molar amount of DPTTC, is comprised between 1.5% and 12%, relative to the total molar amount of monomers used, and preferably the molar amount of compound C6, preferably the molar amount of DPTTC, is comprised between 1.5% and 12%, relative to the total molar amount of unsaturated groups of the monomers used.

5. the polymer A is selected from α,ω-disulfonated polymers A1, α-monosulfonated polymers A2, polymers A3 containing phosphinate groups, polymers A4 containing phosphonate groups, polymers A5 containing phosphinate and phosphonate groups, and combinations thereof, or polymer A has a weight average molecular weight Mw (measured by SEC) of less than 1 million g / mol or less than 800,000 g / mol, preferably less than 400,000 g / mol or less than 200,000 g / mol, more selectively less than 50,000 g / mol or less than 20,000 g / mol, more preferably less than 15,000 g / mol or less than 10,000 g / mol, even more selectively less than 7,000 g / mol or less than 6,000 g / mol, or polymer A has a weight average molecular weight Mw (measured by SEC) greater than 1,000 g / mol or greater than 1,200 g / mol, or Composition T according to any one of claims 1 to 4, in which polymer A has a polymolecularity index IP (measured by SEC) of less than 4 or in the range from 1.2 to 4 or from 1.5 to 4, from 1.2 to 3 or from 1.5 to 3, from 1.2 to 2.5 or even from 1.5 to 2.

5.

6. Composition T according to any one of claims 1 to 5, further comprising, preferably within composition R: compounds D selected from sulfo-carboxy-aromatic and sulfo-carboxy-alkyl acids, preferably 3-sulfopropionic acid, 3-sulfo-2-methylpropionic acid, sulfosuccinic acid, their salts and combinations thereof, or selected from the sodium, potassium, lithium, calcium, magnesium and ammonium salts, preferably the sodium and ammonium salts, a molar amount of compound D, determined according to the method described herein, greater than 2% relative to the molar amount of sulfur IV in compound C1, or A compound F selected from 2-sulfoacetic acid, para-toluenesulfonic acid (PTSA), sulfuric acid, methanesulfonic acid, their salts and combinations thereof.

7. compound B is selected from non-alkoxylated polyols, non-alkoxylated polyamines, non-alkoxylated amino alcohols, non-alkoxylated (polyamino) alcohols, non-alkoxylated amino (poly alcohols), non-alkoxylated oses, non-alkoxylated osides, alkoxylated polyols, alkoxylated polyamines, alkoxylated amino alcohols, alkoxylated (polyamino) alcohols, alkoxylated amino (poly alcohols), alkoxylated oses, alkoxylated osides and combinations thereof, or Compound B is selected from the group consisting of glycerol, polyalkylene glycol (preferably polyalkylene glycol, polypropylene glycol, polybutylene glycol), pentaerythritol, triethanolamine, ethanolamine, diethanolamine, 3-amino-1-propanol, 1-amino-2-propanol, butanetriol, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, pentaerythritol, sorbitol, 5-amino-1-pentanol, 2-(2-aminoethyl)-2-propanol, 2-(2-aminoethyl)-2-propanol, 1 ... (2-methoxy)ethanol, N-(2-aminoethyl)ethanolamine, bis(N-hydroxyethyl)propane-1,3-diamine, diisopropanolamine, triisopropanolamine, N-methyldiethanolamine, N-butyldiethanolamine, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2,3-propanetriol, 1,2-butanediol, 1,4-butanediol, 2,3-butanediol, neopentyl glycol, triethylene glycol, Methylolpropane, 1,2,4-butanetriol, 1,2-pentanediol, 1,5-pentanediol, 1,6-hexanediol, 2,5-dimethyl-2,5-hexanediol, D-arabinose, L-arabinose, D-xylose, D-glucose, D-mannose, D-galactose, D-glucosamine, D-fructose, maltose, sucrose, lactose, ethylenediamine, diethylenetriamine, triethylenetetramine, 1,3-diaminopropane, 1,2-diaminopropane, neopentyldiamine amine, hexamethylenediamine, octamethylenediamine, N-(2-aminoethyl)propane-1,3-diamine, 1,2,3-propanetriamine, N,N-bis(3-aminopropylamine) and combinations thereof, preferably selected from glycerol, triethanolamine, trimethylolpropane, 1,2,4-butanetriol, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, pentaerythritol, sorbitol and combinations thereof; or compound B has a molecular weight ranging from 50 g / mol to 1,000 g / mol, preferably from 55 g / mol to 500 g / mol or from 55 g / mol to 250 g / mol, or the molar amount of functional groups of compound B ranges from 5% to 100%, preferably from 10% to 100%, or from 10% to 90%, or from 20% to 100%, or from 20% to 80%, relative to the total molar amount of carboxyl groups of polymer A, or Composition T according to any one of claims 1 to 6, in which the molar amount of compound B ranges from 5% to 100%, preferably from 10% to 100%, or from 10% to 90%, or from 20% to 100%, or from 20% to 80%, relative to the total molar amount of monomers.

8. does not contain any urea-formaldehyde compounds or any formaldehyde compounds, or any compounds containing phosphorus in the oxidation state I, or any compounds containing phosphorus in the oxidation state III, or any compounds containing phosphorus in the oxidation state V, Composition T according to any one of claims 1 to 7, wherein composition R does not comprise any urea-formaldehyde compounds or any formaldehyde compounds, or any compounds containing phosphorus in the oxidation state I, or any compounds containing phosphorus in the oxidation state III, or any compounds containing phosphorus in the oxidation state V.

9. Composition T according to any one of claims 1 to 8, wherein material E is selected from silicon, lithium, carbon graphite or graphitic carbon, hexagonal carbon, rhombohedral carbon and combinations thereof, optionally doped with at least one element, preferably selected from lithium, germanium, silicon and combinations thereof.

10. - preparation of an aqueous composition R according to any one of claims 1 to 9, the addition of at least one material E chosen from metal fibres, metal particles, carbon graphite fibres, carbon graphite particles and combinations thereof, preferably chosen from silicon, lithium, carbon graphite or graphitic carbon, hexagonal carbon, rhombohedral carbon and combinations thereof, optionally doped with at least one element, preferably chosen from lithium, germanium, silicon and combinations thereof; A method for producing the aqueous composition T according to any one of claims 1 to 9, comprising:

11. An aqueous composition R according to any one of claims 1 to 9.

12. - preparation of a polymer A according to any one of claims 1 to 5, - optionally maintaining or adding to the aqueous dispersion of polymer A at least one compound D chosen from sulfocarboxylic acids, sulfocarboxylates and combinations thereof, the addition of at least one polyfunctional compound B chosen from polyols, polyamines, aminoalcohols, (polyamino)alcohols, amino(polyalcohols), oses, oses and combinations thereof, A method for producing the aqueous composition R according to any one of claims 1 to 9, comprising:

13. at least one α-sulfonated polymer A prepared in water by polymerization reaction of at least one monomer M chosen from acrylic acid, methacrylic acid, acrylates, methacrylates and combinations thereof, in the presence of at least one initiator compound and at least one sulfur compound containing sulfur in oxidation state IV, preferably in the absence of any phosphorus compound; and at least one compound D chosen from sulfocarboxylic acids, sulfocarboxylates and combinations thereof, A crosslinking agent for crosslinking the aqueous composition R according to any one of claims 1 to 11, comprising:

14. at least one aqueous dispersion of an α-sulfonated polymer A prepared in water by polymerization reaction of at least one monomer M chosen from acrylic acid, methacrylic acid, acrylates, methacrylates and combinations thereof, in the presence of at least one initiator compound and at least one sulfur compound containing sulfur in oxidation state IV, preferably in the absence of any phosphorus compound; at least one polyfunctional compound B chosen from polyols, polyamines, aminoalcohols, (polyamino)alcohols, amino(polyalcohols), oses, oses and combinations thereof, Including, The method comprises maintaining or adding to the aqueous dispersion or aqueous composition R of the polymer A at least one compound D selected from sulfocarboxylic acids, sulfocarboxylate salts and combinations thereof, A method for improving the crosslinking properties of an aqueous composition R according to any one of claims 1 to 11.

15. at least one α-sulfonated polymer A prepared in water by polymerization reaction of at least one monomer M chosen from acrylic acid, methacrylic acid, acrylates, methacrylates and combinations thereof, in the presence of at least one initiator compound and at least one sulfur compound C1 containing sulfur in oxidation state IV, preferably in the absence of any phosphorus compound; and at least one compound D chosen from sulfocarboxylic acids, sulfocarboxylates and combinations thereof, The crosslinking improver of the aqueous composition R according to any one of claims 1 to 11, comprising:

16. - applying at least one composition T according to any one of claims 1 to 9 onto a substrate, - crosslinking an impregnating material E with a composition R according to any one of claims 1 to 11, Including, Preferably, at least one of the applying or crosslinking steps is carried out at a pH below 7, preferably below 5, or crosslinking is carried out at a temperature in the range of 100-250°C, preferably 150-240°C or 170-230°C.

17. 17. An anode prepared according to the method of claim 16.

Citation Information

Patent Citations

  • Crosslinkable negative electrode binder composition, negative electrode active material slurry, negative electrode, negative electrode preparation method and lithium ion battery

    CN112993252A

  • (Meth)acrylic acid type polymer and unsaturated polyalkylene glycol type copolymer, and methods for production thereof

    EP1300426A1

  • Binder

    JP2021015778A